ANALISIS FAKTOR YANG MEMPENGARUHI IMPLEMENTASI SISTEM INFORMASI AKUNTANSI KOMPUTERISASI PADA KANTOR PELAYANAN PAJAK PRATAMA LUBUK PAKAM - GRACESIELA YOSEPHINE SIMANJUNTAK (LP2MTBM MAKARIOZ, 2021)
This research aims to test and analyze the Factors That Affect the Implementation of Computerized Accounting InformationSystem at the Office of Primary Tax Services Lubuk Pakam. The data in this study is primary data obtained through thedissemination of questionnaires directly to respondents in KPP Pratama Lubuk Pakam. The population in this study is afiscus working on KPP Pratama Lubuk Pakam. Sampling techniques usingthe purposive samplingmethod. Dependentvariables in this study are The Implementation of Accounting Information Systems, while independent variables areInfrastructure, Human Resources, Cost, Perception of Usefulness, and Ease Perception tested with multiple regressionanalysis using SPSS Version 20 software. The results showed that only infrastructure variables, perception of usefulness,and perception of ease had a significant effect on the implementation of computerized accounting information systems inKPP Pratama Lubuk Pakam. While Human Resources and Costs have no significant effect on the Implementation ofComputerized Accounting Information System at KPP Pratama Lubuk Pakam. The results of the coefficient of determinationshowed that all free variables affected the Computerized Accounting Information System Implementation variable by 67.80%,while the remaining 32.20% was influenced by other variables outside of the study.